Stature: Does it really make a difference in match-play outcomes among professional tennis players? - Sögüt, M. (International Journal of Performance Analysis in Sport, 2018)
The purpose of this study was to determine the effects of body height on match-play characteristics among professional tennis players participated in the 2017 Wimbledon Championships. Anthropometric features and 11 match-play statistics of 119 players (male = 60, female = 59) were obtained from the official web page of the tournament and/or from the ATP and WTA. They were divided into three consecutive sub-groups according to their heights. Results revealed that, regardless of gender, players in the tallest group had significantly produced higher speed on both first and second serve than the players in the other groups. Tallest male players exhibited significantly greater scores on the percentage of first serve points won and aces per set than the players in the shortest group. Conversely, players in the shortest groups achieved significantly more percentage of return point than the players in the tallest groups. Height was found to be significantly and positively correlated with both first and second serve speeds, and aces performed per set and significantly and negatively associated with percentage of return points won in both genders. These findings highlight the considerable advantages and disadvantages of stature on serve and return related match outcomes in a grass court tournament.